Cyclura : natural history, husbandry, and conservation of West Indian rock iguanas - Lemm, Jeffrey M., 1971- (Noyes series in animal behavior, ecology, conservation, and management., 2012)
Rock iguanas of the West Indies are considered to be the most endangered group of lizards in the world. They are a flagship species in the Caribbean and on most islands are the largest native land animals. Unfortunately, human encroachment and introduced animals have brought this species to the brink of extinction. Cyclura: Natural History, Husbandry, and Conservation of the West Indian Iguanas is the first book to combine the natural history and captive husbandry of these remarkable reptiles, while at the same time outlining the problems researchers and conservationists are battling to save.